Behavioral Finance and Asset Prices The Influence of Investor's Emotions - Bourghelle, David; Grandin, Pascal; Jawadi, Fredj; Rozin, Philippe (Cham : Springer International Publishing : Imprint: Springer, 2023)
In recent decades, the financial markets have experienced various crises, shocks and disruptive events, driving high levels of volatility. This volatility is too strong to be fully justified simply by changes in fundamentals. This volume discusses these highly relevant issues with special focus on asset pricing and behavioral finance. Financial price assets of the 2020s appear to be driven by various attractors in addition to fundamentals, and there is no doubt that investor emotions, market sentiment, the news, and external factors such as uncertainty all play a key role. This has been clearly observed in recent years, especially during the ongoing coronavirus pandemic that has changed the common perception of the way financial markets work.
Introduction -- Part I. Asset Pricing -- Chapter 1. Oil Price Uncertainty: Panel Evidence from the G7 and BRICS Countries -- Chapter 2. Climate Risk and the Volatility of Agricultural Commodity Price Fluctuations: A Forecasting Experiment -- Chapter 3. Linking the COVID-19 Epidemic and Emerging Market OAS: Evidence Using Dynamic Copulas and Pareti Distributions -- Part II. Behavioral Finance -- Chapter 4. On the Relevance of Employee Stock Options Behavioral Models -- Chapter 5. the Term Structure of Psychological Discount Rate: Characteristics and Functional Forms -- Chapter 6. An Experimental Analysis of Investor Sentiment -- Chapter 7. On the Evolutionary Stability of Sentiment Investor -- Chapter 8. Institutional Investor Field Research: Company Fundamentals Driven by Investor Attention -- Chapter 9. What Drives the US Stock Market in the Context of COVID-19, Fundamentals or Investors' Emotions?.
Keywords: Economics -- Psychological aspects; Capital market; Finance; Financial services industry; Behavioral Finance; Capital Markets; Financial Economics; Financial Services